Lithosphere Weakening During Arctic Ocean Opening: Evidence From Effective Elastic Thickness. Issue 14 (19th July 2021) - Lu, Yu; Lu, Zhezhe; Li, Chun‐Feng; Zhu, Shuang; Audet, Pascal
Abstract: Evolution of the Arctic Ocean lithosphere has involved multiple stages of opening with crustal stretching and thinning prior to lithospheric breakup. Mapping lateral variations in lithospheric rheology can help unravel the detailed tectonic history of the Arctic. Here we perform a wavelet analysis of gravity and bathymetry data to map the effective elastic thickness ( T e ) of the lithosphere in the Arctic. The low overall T e suggests that large shear stresses and serpentinization weakened the lithosphere at Arctic passive margins during a multistage opening process. Moderately low T e values along the Gakkel Ridge imply a relatively cold ultraslow‐spreading center compared to typical mid‐ocean ridges. Plain Language Summary: Geological exploration and sampling in the Arctic Ocean are difficult due to sea ice cover and frigid weather. Gravity and bathymetry data obtained using remote sensing methods can be used to estimate the effective elastic thickness ( T e ) of the lithosphere, which is a proxy for the strength of the tectonic plates. We draw a new T e map of the Arctic Ocean by combining the latest data with recent crustal structure models. T e is low on the edge of the oceanic basins, suggesting that the lithosphere was weakened by mechanical rifting and mantle metamorphism in the opening of the Arctic Ocean. The seafloor spreading centers are generally thought to be hot and weak, but the Gakkel Ridge shows moderately low T e, revealing unique mechanical and geothermal properties of this slowest spreading center in the world. Key Points: The Arctic effective elastic thickness ( T e ) map is obtained by spectral analysis Sedimentary correction for vertical density variation improves the T e estimation Pre‐breakup lithospheric extension caused low T e along passive margins